Numerical Investigation of Heat Transfer Analysis Using Electromagnetohydrodynamics with Aggregated Nanoparticles - Kameswaran , Peri K.; Lokeshwari, A. (East European Journal of Physics, 2026)
Optimizing heat transmission remains a significant contemporary challenge in modern technological applications. Nanofluids exhibit strong potential thermal conductivity for enhancing heat transfer and improving energy system efficiency. In comparison to dispersed nanoparticles, aggregated nanoparticles are noteworthy for evaluating the thermal behavior of nanoparticles at the nanoscale. In spite of that aggregation effect, the fractal dimension of the aggregated nanoparticles will have a transformative effect on heat transfer. The objective of the present study is to investigate the influence of electromagnetohydrodynamic effects on heat transfer in a nanofluid containing aggregated nanoparticles over an exponentially stretching sheet. The governing equations for momentum and energy are transformed into a system of nonlinear ordinary differential equations with specified boundary conditions. An analytical solution is presented for a specific instance where the electric field parameter is absent. Numerical solutions are achieved for various ranges of physical parameters, and computed results are validated with existing literature. The findings indicate that nanoparticle aggregation leads to thickening the thermal boundary layer and improving heat transfer. In addition to this synergistic effect of aggregation and electric field, it leads to the decrease in velocity profiles. At 5% volume fraction, aggregated nanoparticles provide a heat transfer enhancement of approximately 34% over dispersed nanoparticles. The temperature profiles exhibit a rising trend with an increasing volume fraction. In the presence of aggregated nanoparticles, both the skin friction coefficient and the Nusselt number increase with rising magnetic field strength.